"My Heart Opens and My Spirit Flies": Musical Exemplars of Psychological Flexibility in Health and Healing. (14th May 2013) - Koen, Benjamin D.
Abstract Across several disciplines in the health and social sciences, psychological flexibility is gaining in influence and explanatory power as a conceptual frame to better understand diverse cultural and clinical contexts of health and healing. Although music as a potential primer of psychological flexibility is seldom considered in extant research, key contributions have framed aspects of music's potential efficacy to promote health and healing within the construct of psychological flexibility. Building from this research and from studies in psychology and anthropology concerned with flexibility, and based on field research I conducted in the Pamir Mountain region of Tajik Badakhshan, I explore how the preeminent genre of Pamiri devotional music, known as maddoh, facilitates or primes psychological flexibility for participants. In this case study, priming a state of psychological flexibility is accomplished by engaging specific cultural exemplars found in the natural and built environments, the local belief system, poetry, prayer, and music, creating a multilayered network of flexibility.